Attractive Regional Investment Model for Investors - Winna Roswinna; Maria Lusiana Yulianti; Anne Lasminingrat (DINASTI RESEARCH, 2023)
The primary objective of this research is to analyze the potential of the region's limited natural resources, man-made natural resources, and human resources for marketing purposes. By doing so, the regional government can boost the local economy, reduce reliance on financial aid from the central government, and gradually become self-sufficient. This requires a creative approach to fund allocation, whether from the General Allocation Fund (DAU) or Regional Own Revenue (PAD), in an appropriate and fair manner. The local government must also focus on marketing the region's unique products and creating a competitive advantage to attract investors. The ability to attract Special Allocation Funds from the central government is also crucial for the successful implementation of development programs, both social and economic. Effective marketing of regional potentials can generate profits and benefits for the sustainable welfare of the people in the region. The study revealed that investors consider the physical infrastructure and human resources available in the region when making investment decisions.Regional Potential